A services operations performance measurement framework for multimodal logistics gateways in emerging megaregions. Issue 1 (2nd January 2021) - Paraskevadakis, Dimitrios; Bury, Alan; Ren, Jun; Wang, Jin
ABSTRACT: Gateways in emerging megaregions have the existing transport infrastructure tο support modal shift and deliver sustainable development. To address these issues, there is a need for more efficient traffic management solutions and an accompanying shift away from road transportation towards more environmentally friendly modes both for freight and for passengers. More importantly, an integrated methodological approach needs to be adopted by decision-makers when they assess existing and planned transport infrastructure for its ongoing sustainable development. This research provides a novel approach to the performance evaluation of modal shift and transport infrastructure service quality. The application and combination of Importance-Performance Analysis (IPA) and Analytical Hierarchical Process (AHP) in an intermodal regional case study provides a straightforward methodology for the assessment of sustainable development. In addition, added value is provided to the literature for long term scenarios' planning for sustainable transport infrastructure.